2021
DOI: 10.1080/09540105.2021.1874883
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to walnuts and hazelnuts in atopic dermatitis patients and analysis of sensitization to molecular components

Abstract: Aim: To evaluate the occurrence of food allergy to walnuts and hazelnuts in atopic dermatitis patients. Methods: The examination of specific IgE to molecular components with Multiplex ISAC testing was performed. The diagnosis of food allergy was confirmed in patients suffering from food reactions to walnuts/hazelnuts together with positive results of specific IgE to molecular components. Results and conclusion: : Altogether 100 atopic dermatitis patients were examined-48 men, 52 women, the average age 40.9 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Omalizumab is an anti-IgE monoclonal antibody that works by binding to the Fc region of IgE antibodies, inhibiting receptor binding on mast cells and basophils [53], preventing degranulation and allergic manifestations. It should be initiated before the OIT and continued for a few weeks after [54].…”
Section: Omalizumabmentioning
confidence: 99%
“…Omalizumab is an anti-IgE monoclonal antibody that works by binding to the Fc region of IgE antibodies, inhibiting receptor binding on mast cells and basophils [53], preventing degranulation and allergic manifestations. It should be initiated before the OIT and continued for a few weeks after [54].…”
Section: Omalizumabmentioning
confidence: 99%
“…Study of IgE specificity revealed an association of sensitization to molecular components of pollen allergens with food reactions in patients suffering from atopic dermatitis. In patients suffering from reactions to peanuts, hazelnuts, celery, apple and peach, a significantly higher frequency of sensitization to major pollen allergens Bet v 1, Aln g 1, Phl p 1, 2, 4, 5, 6, 11 was found ( Čelakovská et al, 2021a ; Čelakovská et al, 2021b ). Interestingly, sensitization to Bet v 1 homologues and profilins is associated with mild symptoms (pollen eating syndrome), and sensitization to LTP homologues and seed storage proteins are associated with severe reactions ( Čelakovská et al, 2021a ).…”
Section: Sensitization To Pollen Allergensmentioning
confidence: 99%
“…Omalizumab is an anti-IgE monoclonal antibody. It works by binding to the Fc region of IgE antibodies, blocking the binding to specific receptors on mast cells and basophils [59,60,68], preventing their degranulation and therefore the appearance of allergic manifestations. Omalizumab should be initiated before the OIT and continued for a few more weeks in parallel [31,69,70].…”
Section: Omalizumabmentioning
confidence: 99%